Computational modeling of cyclotides as antimicrobial agents against Neisseria gonorrhoeae PorB porin protein: integration of docking, immune, and molecular dynamics simulations - Hussain, Muzamal; Kanwal, Nazia; Jahangir, Alishba; Ali, Nouman; Hanif, Nimra; Ullah, Obaid (Frontiers in Chemistry, 2024)
Background Neisseria gonorrhoeae is the bacterium responsible for gonorrhoea, one of the most common sexually transmitted infections (STIs) globally. In 2020, the World Health Organization (WHO) estimated 82.4 million new cases of Neisseria gonorrhoeae infections. Current treatments rely on antibiotics, but the emergence of multi drug resistance (MDR) strains poses a significant threat to public health. This research aims to use computational modeling of cyclotides as antimicrobial agents targeting the Neisseria gonorrhoeae PorB Porin protein to inhibit its pathogenicity. Methodology The PorB Porin protein was retrieved from the Protein Data Bank (PDB ID: 4AUI), cleaned, and visualized using Discovery Visual Studio. Physicochemical properties were predicted using ProtParam. Cyclotides were obtained from the CyBase database, with 3D models generated and refined via the Swiss Model for docking studies. HDOCK was used for molecular docking. Toxicity and allergenicity predictions were performed with ToxinPred and AlgPred. A heatmap of the peptide was created using Protein-Sol. Molecular dynamics (MD) simulations were conducted for 100,000 picoseconds using Desmond from Schrödinger LLC, while binding energy was analyzed using MMGBSA. Immune response simulations were done with C-ImmSim 10.1, and peptide simulation in water was performed via WebGro. Results The protein’s GRAVY value is −0.539, indicating moderate hydrophilicity, and its isoelectric point is 9.14, suggesting a fundamental nature. Globa D had the highest docking score (−270.04 kcal/mol) and was deemed non-toxic and non-allergenic. MD simulations showed stable protein-ligand interactions, and MMGBSA revealed a low binding energy of −36.737 kcal/mol. Immune simulations indicated an effective immune response and peptide simulations demonstrated Globa D’s stability in water, making it a potential candidate for pharmaceutical applications. Conclusion Globa D proved the best drug candidate against Neisseria gonorrhoeae by inhibiting PorB Porin protein chain A. Further in vitro and in vivo studies are recommended to validate these findings and explore clinical applications.